2016
DOI: 10.1039/c6ra05895g
|View full text |Cite
|
Sign up to set email alerts
|

Single nanoparticle plasmonic spectroscopy for study of the efflux function of multidrug ABC membrane transporters of single live cells

Abstract: ATP-binding cassette (ABC) membrane transporters exist in all living organisms and play key roles in a wide range of cellular and physiological functions. The ABC transporters can selectively extrude a wide variety of structurally and functionally unrelated substrates, leading to multidrug resistance. Despite extensive study, their efflux molecular mechanisms remain elusive. In this study, we synthesized and characterized purified silver nanoparticles (Ag NPs) (97 ± 13 nm in diameter), and used them as photost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…Furthermore, we used the LSPR spectra and scattering intensity of single NPs to characterize the size and number of single NPs, and monitor the peptides functionalized on the surface of the NPs in situ in real time as they are incubated with the cells and transported across the cellular membrane over time using the similar approaches as we reported previously. 2932, 4344 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, we used the LSPR spectra and scattering intensity of single NPs to characterize the size and number of single NPs, and monitor the peptides functionalized on the surface of the NPs in situ in real time as they are incubated with the cells and transported across the cellular membrane over time using the similar approaches as we reported previously. 2932, 4344 …”
Section: Resultsmentioning
confidence: 99%
“…The results show that 94% of WT and 95% of ΔBmrA cells incubated with the positively charged NPs over 2 h are alive, and 98% of either WT or ΔBmrA cells incubated with the negatively charged NPs over 2 h are alive (Figure 8C), which are similar to what we observed previously using citrated Ag NPs. 29, 43 Notably, the cells with the NPs are all alive. This result shows that both positively and negatively charged Ag-peptide NPs (1.4 nm) are biocompatible to the cells, and the NPs are well suited to serve as optical imaging probes for real-time study of charged-dependent efflux function of BmrA membrane transporter of single live cells The results further demonstrate that accumulation of the NPs in single live cells is not attributed to the disintegration of cellular membrane due to the cell death, because the cells with the NPs are alive.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have demonstrated that we can image and characterize the sizes of single Ag NPs at nanometer (nm) resolution in single live cells in situ in real time using size-dependent localized surface plasmon resonance (LSPR) spectra of single Ag NPs by dark-eld optical microscopy and spectroscopy (DFOMS). [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] We have used the size-dependent LSPR spectra of single Ag NPs to track the transport of single NPs in and out of single live cells and to determine the pore sizes of membrane transporters. 29,30 In our previous studies, we found dose and size dependent inhibitory effects of antibiotic nanocarriers (AgMUNH-Ox NPs) against Pseudomonas aeruginosa (Gram-negative bacterium) and Bacillus subtilis (Gram-positive bacterium).…”
Section: Introductionmentioning
confidence: 99%